3f+2=4f+4

Simple and best practice solution for 3f+2=4f+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3f+2=4f+4 equation:


Simplifying
3f + 2 = 4f + 4

Reorder the terms:
2 + 3f = 4f + 4

Reorder the terms:
2 + 3f = 4 + 4f

Solving
2 + 3f = 4 + 4f

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-4f' to each side of the equation.
2 + 3f + -4f = 4 + 4f + -4f

Combine like terms: 3f + -4f = -1f
2 + -1f = 4 + 4f + -4f

Combine like terms: 4f + -4f = 0
2 + -1f = 4 + 0
2 + -1f = 4

Add '-2' to each side of the equation.
2 + -2 + -1f = 4 + -2

Combine like terms: 2 + -2 = 0
0 + -1f = 4 + -2
-1f = 4 + -2

Combine like terms: 4 + -2 = 2
-1f = 2

Divide each side by '-1'.
f = -2

Simplifying
f = -2

See similar equations:

| 60(12+2.5m)=1 | | 20k+100=10k+120 | | 4x+5(5+x)=-2 | | 2-x=5x+14 | | 6(-m-8)+4(6m+4)=2m+13-4m | | 4y+3-3y=6 | | 3r^2+2r-3=0 | | 5n+1/8=3n-5/4 | | -7x-5=-33 | | -1(3-10y)=12 | | 5p-7=2p-4 | | 4g+6=2g+14 | | 4x^2+16x-15=0 | | t+(-14)= | | 7-4*x=13 | | -4y+7=-21 | | 3b-4=5b-2 | | 9-5n=30 | | 4(b-2)=2(b-6) | | 7x-(4x-6)=30 | | 6r-(-2r-27)=21 | | 19-4c= | | 18=10+4x+4 | | 6y-2=14y+62 | | 7x+9=-29 | | 9=x-3 | | 6y-2=14y+64 | | 3h+1=3(h+1) | | 7x-7=49 | | 2(x-1)-3(x+2)=8 | | 8(12)-18=n | | y=.03x+200 |

Equations solver categories